Silk material modification and microfabrication strategies for applications in biosensors and drug delivery. - Tsioris, Konstantinos. (2017)
Abstract: Silk has proven to be a promising biomaterial for the development of a novel generation of biomedical devices due to the material's intrinsic properties of biocompatibility and biodegradability. To further the development of silk-based devices, augmented functionality can be provided to silk by means of microfabrication and material functionalization. In this dissertation, we set out to explore possibilities of silk-based biomedical device development with particular attention to different fabrication strategies that can be leveraged for this purpose, taking inspiration from conventional lithography, contact imprinting and chemical modification of the silk biomaterial. In particular, we have produced a novel silk-based drug delivery device, in the form of microneedles. For this purpose we have developed micromolding strategies which allow the fabrication of high aspect ratio silk structures. Furthermore, we have produced a THz split ring resonator based sensor device on silk films. To realize this device, we have developed a convenient fabrication method, allowing transfer of previously microfabricated metal and oxide microstructures to the silk film surface. This method has proven useful for hard masking and patterning silk films with reactive ion etching. Moreover, we have explored patterning semiconductor and glass substrates with silk films. For this purpose we have modified a standard microfabrication method -lift off- to be amendable to silk. Furthermore, combining silk based fabrication and material functionalization has lead to microfluidics pH sensing applications. Finally we have explored the possibility of utilizing silk for injectable and biodegradable glucose sensors. For this purpose, we have doped silk hydrogels with a fluorescence based protein biosensor. The advanced silk fabrication and material synthesis strategies and the resulting novel devices presented here could potentially lead to a new class of biomedical applications.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Biomedical Engineering.; Advisors: Fiorenzo Omenetto, and David Kaplan.; Committee: Gary Leisk, and Luca Negro.; Keywords: Biomedical engineering, and Materials Science.